2017
DOI: 10.1371/journal.pone.0177868
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced disseminated pythiosis in BALB/c mice: A new experimental model for Pythium insidiosum infection

Abstract: Pythiosis is a severe and life-threatening disease that affects humans and various animal species. We report a model of vascular/disseminated pythiosis occurring after subcutaneous inoculation of 2 x 104 Pythium insidiosum zoospores/mL in immunocompromised BALB/c mice. For this model, we carried out two rounds of experiments. First, we evaluated two protocols of immunosuppression before inoculation: cyclophosphamide at 150 mg/kg (CYP group) and cyclophosphamide 200 mg/kg plus hydrocortisone acetate at 250 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…In the experimental model of pythiosis in rabbits, the subcutaneous lesions and histopathological findings resemble those observed in horses and other animals presenting the cutaneous form of pythiosis . Histologically, we observed that the oomycete proliferated by invading blood vessels and forming thrombi; these histological findings resemble those seen in human patients and experimentally infected mice . During the progression of vascular human pythiosis, the pathological findings revealed hyphae invading the arterial wall, with eosinophil infiltration and forming thrombi that affect the circulation and usually lead to limb amputation .…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In the experimental model of pythiosis in rabbits, the subcutaneous lesions and histopathological findings resemble those observed in horses and other animals presenting the cutaneous form of pythiosis . Histologically, we observed that the oomycete proliferated by invading blood vessels and forming thrombi; these histological findings resemble those seen in human patients and experimentally infected mice . During the progression of vascular human pythiosis, the pathological findings revealed hyphae invading the arterial wall, with eosinophil infiltration and forming thrombi that affect the circulation and usually lead to limb amputation .…”
Section: Discussionsupporting
confidence: 67%
“…9 Histologically, we observed that the oomycete proliferated by invading blood vessels and forming thrombi; these histological findings resemble those seen in human patients and experimentally infected mice. 12,30 During the progression of vascular human pythiosis, the pathological findings revealed hyphae invading the arterial wall, with eosinophil infiltration and forming thrombi that affect the circulation and usually lead to limb amputation. 30 Dissemination to internal organs can occur when the infection reaches a main artery (ie the iliac artery, aorta, or renal artery), and the patient usually dies of systemic pythiosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All mice were rendered neutropenic by the intraperitoneal administration of cyclophosphamide (CYP, 100 mg/kg of body weight; Genuxal, Baxter Hospitalar Ltd., Brazil) on days Ϫ4 and Ϫ1 preinfection (16). On day 0, the mice were anesthetized by an intraperitoneal injection of ketamine-xylazine (Syntec Brasil Ltd., Brazil) administered at doses of 50 and 10 mg/kg, respectively, and were infected by subcutaneous injections of 2 ϫ 10 4 zoospores/mouse (17).…”
mentioning
confidence: 99%